EXPLORING THE APPLICATION OF INTERTEXTUALITY IN MEDIA DISCOURSE (Konferensiyalar | Conferences, 2024)
Intertextuality gains particular significance in contemporary media practices. It represents a complex mechanism of textual interaction that contributes to the creation of new meanings and enrichment of media discourse content. This article provides an overview of the theoretical aspects of intertextuality, as well as its functions and strategies of application in the media space.